Physical properties of ambient and laboratory‐generated secondary organic aerosol. Issue 12 (17th June 2014) - O'Brien, Rachel E.; Neu, Alexander; Epstein, Scott A.; MacMillan, Amanda C.; Wang, Bingbing; Kelly, Stephen T.; Nizkorodov, Sergey A.; Laskin, Alexander; Moffet, Ryan C.; Gilles, Mary K.
Abstract The size and thickness of organic aerosol particles collected by impaction in five field campaigns were compared to those of laboratory‐generated secondary organic aerosols (SOA). Scanning transmission X‐ray microscopy was used to measure the total carbon absorbance (TCA) by individual particles as a function of their projection areas on the substrate. Particles with higher viscosity/surface tension can be identified by a steeper slope on a plot of TCA versus size because they flatten less upon impaction. The slopes of the ambient data are statistically similar indicating a small range of average viscosities/surface tensions across five field campaigns. Steeper slopes were observed for the plots corresponding to ambient particles, while smaller slopes were indicative of the laboratory‐generated SOA. This comparison indicates that ambient organic particles have higher viscosities/surface tensions than those typically generated in laboratory SOA studies.